Assessment of the Efficiency for some Disinfectants Against the Microorganisms Isolated From the Wards of Newborn and Premature Babies in Baghdad Teaching Hospital - hassan, Yasameen (Iraqi National Journal of Nursing Specialties, 2015)
Objective : To assess the efficiency for some disinfectants against the microorganisms isolated from the wards of newborn and premature babies in Educational Baghdad Hospital . Methodology :This study had done from 1\8\2014 untile 1\9\2014, we had selected three types of disinfectants ( Incidine , Bleach and Microbac Forte )which were used for disinfection in the wards of newborn babies at Educational Baghdad Hospital to assess their effect against the microorganisms isolated from these wards and study the mixed affect of these disinfectants againt same microorganisms . Results : The results of the present study showed that there is affect of the different concentrations of the used disinfectants against the microorganisms isolated from the wards of the newborn and premature babies , also there is a synergism affect of microbac forte with sodium hypochlorite and incidine , as well as , there is an antagonism affect of sodium hypochlorite with incidine a comparision if they used alone . Recommendation : The present study had been suggested to use the highly concentrations of Microbac forte , Incidine and sodium hypochlorite to sterilize the wards of newborn and premature babies , also the study had been suggested to use the mixed solutions of microbac forte with incidine and sodium hypochlorite to disinfect the same wards .